2020
DOI: 10.1002/cb.1894
|View full text |Cite
|
Sign up to set email alerts
|

The impact of expertise on hedonic escalation: A moderating role of regulatory focus

Abstract: This research conducted two experiments to examine the effects of expertise and the regulatory focus on hedonic escalation when consuming various products within a brand. Study 1 showed that expertise results in different levels of hedonic escalation. Novice consumers experienced higher hedonic escalation than expert consumers did, considering their knowledge of products. Study 2 verified the moderating role of regulatory focus on the relationship between expertise and hedonic escalation. It revealed that prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Consumption can be divided into two types according to different consumption goals and product types purchased, namely, hedonic and utilitarian consumption (Chang et al, 2021; Jee, 2021; Khan & Dhar, 2010; Kong et al, 2020). Hedonic consumption refers to the facets of consumer behavior that relate to the multisensory, fantasy, and emotive aspects of product usage experience (Hirschman & Holbrook, 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumption can be divided into two types according to different consumption goals and product types purchased, namely, hedonic and utilitarian consumption (Chang et al, 2021; Jee, 2021; Khan & Dhar, 2010; Kong et al, 2020). Hedonic consumption refers to the facets of consumer behavior that relate to the multisensory, fantasy, and emotive aspects of product usage experience (Hirschman & Holbrook, 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The promotion focus individuals pay attention to the positive effects and experience more emotions related to happiness and depression in the face of the results, while the prevention focus individuals pay attention to negative effects, fulfill personal responsibilities and obligations and experience more emotions related to calm or anxiety in the face of results (Li et al, 2014). Sha et al (2013) found that customer regulatory focus had a significant moderating effect on the relationship between commercial agglomeration impressions and customer identification; based on the data of 416 online shopping consumers, Li et al (2014) found that customer regulatory focus played a moderating role in the positive impact of online service scenarios on customer flow experience; Liu (2015) further examined the different effects of tourists' promotion and prevention focus on purchase intentions; Chang et al (2020) explored the influence of customer regulatory focus on hedonic upgrades in the context of consumers buying different products of the same brand; Huang et al (2020) explored the influence of consumer regulatory focus on their willingness to adopt smart hardware, and found that if promotion focus consumers were promoted to adopt result simulation strategies, while the prevention focus consumers adopted recall analogy strategies, it can effectively improve consumers' willingness to adopt smart hardware. It can be seen that the existing research results are mostly based on the regulatory focus theory to explore the influence of different regulatory focus characteristics on individual purchase intention or behavior (Sha et al, 2013;Li et al, 2014;Liu, 2015;Chang et al, 2020;Huang et al, 2020), and the relevant applications of regulatory focus in the field of enterprise CRM and customer extra-role behavior are less involved.…”
Section: Regulatory Focus Theorymentioning
confidence: 99%
“…Regulatory focus refers to a specific tendency or way that an individual shows in the process of controlling and changing his or her own thoughts or reactions in order to achieve a certain goal ( Avnet and Higgins, 2006 ), and individual preferences and specific decision-making processes will be affected by their own regulatory focus ( Chang et al, 2020 ). The regulatory focus theory distinguishes two different self-regulation methods of promotion focus (PROF) and prevention focus (PREF) ( Higgins, 1998 ).…”
Section: Related Research Reviewsmentioning
confidence: 99%
“…Furthermore, the regulatory orientation literature has examined a wide range of stimuli (such as product type and message framing) to induce regulatory fit (Aaker & Lee, 2006; Ashraf et al, 2016; Chernev, 2004). Specifically, past research suggests that promotion‐oriented (prevention‐oriented) individuals value hedonic (utilitarian) experiences and product attributes (Ashraf & Thongpapanl, 2015; Chang et al, 2021). So far, the interaction effect of these two factors has never been investigated in the context of perceived deception.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, consumer behavior research has established that individuals' decisions are influenced by their regulatory orientation (Ashraf & Thongpapanl, 2015; Chang et al, 2021; Wang & Lee, 2006). Higgins (1997) proposed that self‐regulation involves two separate systems: a promotion system and a prevention system.…”
Section: Introductionmentioning
confidence: 99%